Policy advocacy in waste management through TPS3R in Abiansemal Village, Badung Regency, Bali Province - Yudartha, I Putu Dharmanu; Lukman, Juwita Pratiwi; Ariani, Desak Made; Aprilia, Luh Lisna; Cantika Dewi, Ni Komang Feby; Ari Esta, Puput Fera (West Science Social and Humanities Studies, 2025)
Waste management based on the Reduce, Reuse, Recycle (TPS3R) Waste Management Site is one of the strategic efforts implemented at the village level, such as in Abiansemal Village, Badung Regency, Bali Province. This study analyzes the challenges and opportunities in implementing TPS3R-based waste management policies using the Advocacy Coalition Framework (ACF). The ACF identifies advocacy coalitions of actors with similar interests, beliefs, and values in driving policy change. The study results show various problems in the management of TPS3R, including a lack of public awareness, limited infrastructure and facilities, lack of sustainable funding, and weak institutions. External factors, such as regulatory changes and global pressures, affect policy effectiveness. ACF's analysis reveals that multi-stakeholder collaboration, including government, private sector, and community, is essential to achieve the sustainability of these programs. The solutions offered include increasing public awareness, strengthening infrastructure, adopting community-based business models, building institutional capacity, and coordination between stakeholders. With effective implementation, TPS3R can become a model for sustainable waste management at the village level, supporting the achievement of environmental targets and sustainable development.